Tacit Managerial versus Technical Knowledge As Determinants of Audit Expertise in the Field - Tan, Hun-Tong; Libby, Robert (Journal of Accounting Research, 1997)
Auditing, Audit expertise, Tacit knowledge, Technical knowledge